2017
DOI: 10.5271/sjweh.3658
|View full text |Cite
|
Sign up to set email alerts
|

Work–family conflict and depressive complaints among Dutch employees: examining reciprocal associations in a longitudinal study

Abstract: Insight into the reciprocal association between both directions of work-family conflict and depressive complaints is lacking. This study shows that there is a cross-lagged association between home-work interference and depressive complaints over time, suggesting a partly reciprocal association. This finding suggests that prevention of home-work interference and depressive complaints is important since the two may aggravate each other over time.Affiliation:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 39 publications
0
21
1
3
Order By: Relevance
“…Unfortunately, we could not estimate the effect of private-life roles interfering with work on cardiovascular health. Research shows that these reciprocal forms of conflicts, WLC and Life-Work Conflict, are distinct but related constructs [ 37 ]. Conflicts arising from private-life factors may have different effects on health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, we could not estimate the effect of private-life roles interfering with work on cardiovascular health. Research shows that these reciprocal forms of conflicts, WLC and Life-Work Conflict, are distinct but related constructs [ 37 ]. Conflicts arising from private-life factors may have different effects on health.…”
Section: Discussionmentioning
confidence: 99%
“…Conflicts arising from private-life factors may have different effects on health. For example, Bergs et al [ 37 ] found conflicts arising from private life had an effect on later depressive complaints, while conflicts arising from work did not. Also, we have no information on the effects of work facilitating private-life roles ("work-life balance"), which is also considered a distinct dimension of the interaction between work and private life [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Les conséquences de ces conflits, notamment en lien avec l'insatisfaction dans la vie conjugale et familiale et les loisirs, ainsi qu'en lien avec l'épuisement, l'anxiété, la dépression, le stress et les troubles du sommeil, sont bien documentées (Davis et al, 2017;Kossek et al, 2011;Mansour et Mohanna, 2018). Sur le plan organisationnel, les répercussions concernent surtout la dégradation du climat de travail, la diminution du rendement, de la motivation et de l'implication et une augmentation des accidents du travail, des maladies professionnelles et des invalidités au travail (Bergs et al, 2018;Duxbury et Higgins, 2012;Mansour et Tremblay, 2018;McCutcheon et Morrison, 2017). Le conflit travail-vie personnelle peut nuire également à la qualité des services, particulièrement dans le secteur hôtelier où elle est un avantage concurrentiel (Mansour et Mohanna, 2018).…”
Section: Le Conflit Travail-vie Personnelleunclassified
“…Le conflit travail-vie personnelle peut nuire également à la qualité des services, particulièrement dans le secteur hôtelier où elle est un avantage concurrentiel (Mansour et Mohanna, 2018). Au sens plus large, les conflits entre le travail et la vie personnelle ont des impacts négatifs sur la société, plus particulièrement, sur le système de santé avec une augmentation des consultations médicales, des visites à l'urgence et des chirurgies (Bergs et al, 2018).…”
Section: Le Conflit Travail-vie Personnelleunclassified
See 1 more Smart Citation